1989
DOI: 10.1530/acta.0.1210259
|View full text |Cite
|
Sign up to set email alerts
|

Estrogen biosynthesis in human uterine adenomyosis

Abstract: Abstract. Estrogen biosynthesis (aromatase activity) was investigated in human adenomyosis tissue and compared with that of the normal myometrium, endometrium, and endometrial cancer tissues. Homogenates were incubated with [1,2,6,7-3H]androstenedione and NADPH at 37° C for 1 h. After stopping the enzymatic reaction with ethyl acetate, [4-14C]estrone and [4-14C]estradiol-17β were added to the incubated sample. Estrone and estradiol were purified and identified by Bio-Rad AG1-X2 column chromatography, thin-laye… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
20
0
1

Year Published

1994
1994
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 48 publications
(22 citation statements)
references
References 0 publications
1
20
0
1
Order By: Relevance
“…Steroid hormones have also been implicated in the pathogenesis of uterine adenomyosis, and local rather than systemic hyperestrogenism may be implicated (71). This may be through the action of aromatase on androgen precursors (72) or estrone sulphatase acting to convert estrone-3-sulphate to estrone (73); mRNA for aromatase cytochrome P450 was localized in adenomyotic tissue homogenate, and the P450 aromatase protein was localized in adenomyosis glands (74).…”
Section: Hormonal Abnormalitiesmentioning
confidence: 99%
“…Steroid hormones have also been implicated in the pathogenesis of uterine adenomyosis, and local rather than systemic hyperestrogenism may be implicated (71). This may be through the action of aromatase on androgen precursors (72) or estrone sulphatase acting to convert estrone-3-sulphate to estrone (73); mRNA for aromatase cytochrome P450 was localized in adenomyotic tissue homogenate, and the P450 aromatase protein was localized in adenomyosis glands (74).…”
Section: Hormonal Abnormalitiesmentioning
confidence: 99%
“…Whether ovarian steroid hormones play an essential role in the growth of leiomyoma is unknown. The mitogenic effects of steroid hormones are induced through their receptors or by regulation of growth factor expression (7,8). The UL development possibly occurs in response to a certain type of injury to the myometrium, such as hypoxia (21).…”
Section: Discussionmentioning
confidence: 99%
“…Evidence has shown that leiomyoma tissue is more sensitive to estrogen compared to myometrium and the concentration of estrogen in leiomyoma tissue is higher compared to the normal myometrium. Additionally, the leiomyoma growth is regulated by serum estrogen and estrogen in the tumor (7).…”
Section: Introductionmentioning
confidence: 99%
“…In brief, danazol probably interacts with estrogen, progesterone and/or androgen receptors [18][19][20][21] and directly inhibits enzymes such as 3ß-hydroxysteroid dehydogenase, aromatase, and 17ß-hydroxysteroid dehydrogenase, which are involved in estrogen synthesis, which may have an impact on the growth of endometrial cancer [22][23][24].…”
Section: Discussionmentioning
confidence: 99%